Amelanotic melanoma presented as an ulcerated, exophytic mass on the mandibular ridge - Azañero, Wilson Alejandro Delgado; Parra, Jaime Orlando Huamaní; Rivadeneira, Leopoldo Victor Meneses; Rojas, Claudia Gabriela Ruiz; Valdez, Luciano Hermios Matos; Sanchez, Katman Bear Toledo (Journal of Oral Diagnosis, 2025)
Amelanotic melanomas are aggressive neoplasms that are exceedingly rare in the oral cavity. We report the case of a 74-year-old woman who presented with a large, ulcerated, exophytic mass on the edentulous lower alveolar ridge. Histological examination revealed two distinct cell populations: epithelioid cells arranged in an alveolar pattern and spindle-shaped cells arranged in fascicles, both exhibiting prominent nucleoli. Immunohistochemical staining was performed using S-100, SOX10, Melan-A, HMB-45, PRAME, and Ki-67. S-100 and SOX10 showed strong positivity, PRAME was focally positive, and the Ki-67 index was high. Melan-A and HMB-45 were negative. Due to the absence of clinical and histological pigmentation, amelanotic melanoma can be easily overlooked. Therefore, any rapidly growing, ulcerated mass in the oral cavity should raise suspicion for this diagnosis.